1991
DOI: 10.1095/biolreprod44.5.842
|View full text |Cite
|
Sign up to set email alerts
|

Presence and Role of c-myc Proto-oncogene Product in Mammalian Sperm Cell Function1

Abstract: The presence and role of c-myc protein was investigated in mature sperm cells of the human, mouse, and rabbit. The monoclonal antibodies against c-myc protein (c-myc) reacted with the acrosomal region of the sperm of these mammalian species in the indirect immunofluorescence technique. The c-myc monoclonal antibody (MCA) recognized c-myc protein of 62 and 64 kDa on Western blots of lithium diiodosalicylate-solubilized sperm preparations of these species. The c-myc MCA showed a dose-dependent inhibition of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…In goat spermatozoa, the protein kinases phosphorylated only serine and threonine residues [18,22] but in addition to these residues phosphotyrosine was also detected in certain phosphoproteins of spermatozoa of mouse, rat, rabbit, boar and man [1,18,27]. In the present study, phosphoamino acid analysis of the phosphorylated acrosomal membrane proteins of hamster spermatozoa indicated that phospho-tyr was the predominant residue although phospho-ser and phospho-thr were also present in trace amounts ( Fig.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…In goat spermatozoa, the protein kinases phosphorylated only serine and threonine residues [18,22] but in addition to these residues phosphotyrosine was also detected in certain phosphoproteins of spermatozoa of mouse, rat, rabbit, boar and man [1,18,27]. In the present study, phosphoamino acid analysis of the phosphorylated acrosomal membrane proteins of hamster spermatozoa indicated that phospho-tyr was the predominant residue although phospho-ser and phospho-thr were also present in trace amounts ( Fig.…”
Section: Resultssupporting
confidence: 54%
“…However, as yet, the molecular basis underlying the sperm acrosome reaction is not clearly understood. Recent studies have clearly indicated that phosphorylation of proteins in spermatozoa, especially at the tyrosine residue, is an important regulatory event that modulates events associated with capacitation such as the acrosome reaction and fertilizing ability of spermatozoa [1][2][3]. Further, inhibition of protein tyrosine kinase activity was observed to prevent acrosomal exocytosis [4] and the fertilizing ability of spermatozoa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our results suggest a weak but a potential function of some transcripts during capacitation and/or acrosome reaction. c-myc, which was one of the first transcripts described in spermatozoa [14] and the protein corresponding reported in human sperm cells [15], has been carefully studied, and we have observed an incomplete or total disappearance of cmyc transcripts after 4 h of capacitation without modification of the mRNA encoding Prm-2. Moreover, the levels of c-myc transcripts are roughly identical with those before capacitation when spermatozoa are incubated with cycloheximide.…”
Section: Significance Of Transcripts In Spermatozoa and Future Develomentioning
confidence: 71%
“…18 There are some studies researching the levels of different transcripts of mRNA encoding molecules containing nuclear condensation, capasity and sperm function of spermatozoa. 19,20 In these studies, it has been submitted that the quality of sperm can be related with its mRNA distribution. Also in same other studies, it has been concluded that human semen with low quality is related with abnormal sperm mRNA content for certain genes.…”
Section: Discussionmentioning
confidence: 99%